Perspective on the Role of Academic Journals on Scientific Colonialism in Paleontology - Chacon-Baca, Elizabeth; Moreno, Karen; Sterli, Juliana; Buldrini, Karina E.; Chacaltana Budiel, César Augusto; Echevarría, Javier; de Araújo Júnior, Hermínio Ismael; Ghilardi, Renato Pirani [UNESP]; Tejada-Medina, Luz Marina; Zurita-Altamirano, Daniel (Taylor & Francis, 2023)
Academic journals have developed policies that globally regulate the specific protocols that must be followed when using sensitive medical, biological, chemical, and genetic data in research. Yet, paleontological material seems to be excluded. We performed a submission policy search to test the extent of this legal gap in light of colonialism. Results show that, even though most journals adhere to broad ethical guidelines, they do not systematically provide information regarding fossil permits and specifications on their collection and storage, as well as other relevant data (N = 108, > 80% in Asia and North America, > 65% in Europe and Latin America). This problem impacts educational, economical, and scientific development, perpetuates illegal trafficking, and boosts scientific colonialism. It is necessary to implement a mandatory policy for fossil handling, including ethical and legal management in the submission guidelines of journals, and to request that this information is included in materials and method sections.
Keywords: academic colonialism; Colonial paleontology; ethics; fossil legislation; geoheritage